2012
DOI: 10.4028/www.scientific.net/msf.727-728.61
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Characterization of β-Ti Alloys by Means of Powder Metallurgy Processing and Blender Elemental

Abstract: Titanium is an increasingly used material on industry. Based on Ti and titanium alloys characteristics, one of the most favorable processing methods is the powder metallurgy. Attending to microstructure, alloys showing β phase have singular characteristics of low elastic modulus, good specific properties and high corrosion resistance, which make β-Ti alloys very appropriated for specific uses covering a width list of fields including aeronautics or biomaterials. At this work, it has been obtained and character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…These alloys have been obtained by means of blending elemental powders and powder metallurgy process as mentioned elsewhere [14]. Samples were provided in form of disks of 25 mm in diameter and 3 mm thick.The specimens were not polished before testing, they were used as received, ultrasonically cleaned with acetone and ethanol for 5 minutes respectively in order to remove any existing particle from the pores, and air-dried.…”
Section: Experimental 21materials and Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…These alloys have been obtained by means of blending elemental powders and powder metallurgy process as mentioned elsewhere [14]. Samples were provided in form of disks of 25 mm in diameter and 3 mm thick.The specimens were not polished before testing, they were used as received, ultrasonically cleaned with acetone and ethanol for 5 minutes respectively in order to remove any existing particle from the pores, and air-dried.…”
Section: Experimental 21materials and Solutionmentioning
confidence: 99%
“…An homogeneous microstructure is achieved even though all the diffusion process is conducted in solid state [13]. Sn favors to the titanium-niobium due to its relatively low melting point and form a liquid phase in the sintering phase [14]. However, it has been also shown that Sn dissolves preferentially in the Ti30Nb alloys, decreasing the corrosion resistance when adding above 2% in Sn [15].…”
Section: Introductionmentioning
confidence: 99%
“…It avoids the remelting of the material and subsequent heat treatments performed in the fusion process [19]. Nowadays porous titanium has become a popular surgical implant material since it increases the roughness and the porosity of the material, thus increasing the integration of the material device to the bone [18][19][20]. As the roughness increases the osseointegration is greater, but the active surface is also higher promoting the corrosion and the formation of oxides on the titanium surface [16,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…An homogeneous microstructure is achieved even though all the diffusion process is conducted in solid state [9]. On the contrary, Sn helps to the titaniumniobium diffusion spread as it has a relatively low melting point and form a liquid phase in the sintering phase [23] [18]. Regarding the phase diagrams of Ti-Nb alloys, it is necessary a minimum of 25 %at.…”
Section: Introductionmentioning
confidence: 99%